Prognosis of cryptogenic fibrosing alveolitis. Issue 5 (May 1983) - Tukiainen, P; Taskinen, E; Holsti, P; Korhola, O; Valle, M
Abstract : We have analysed retrospectively 100 consecutive patients with cryptogenic fibrosing alveolitis, who were treated with corticosteroids and followed for at least three years. At the time of diagnosis biopsy specimens were available in 64 cases. The clinical, radiographic, physiological, and histological features and the response to steroid treatment have been correlated with the prognosis. An early objective functional improvement was observed in 30%. Analysis of the survival data (life table and log rank test) showed a longer survival in younger patients and in patients with a shorter duration of symptoms before presentation, less radiographic abnormality, and less impairment of diffusing capacity, but not clearly in patients with more cellular histological appearances. The most favourable prognostic sign seemed to be an early response to steroid treatment.